Fibroblast Growth Factors in the Management of Acute Kidney Injury Following Ischemia-Reperfusion - Deng, Lian-Cheng; Alinejad, Tahereh; Bellusci, Saverio; Zhang, Jin-San (Frontiers in Pharmacology, 2020)
Ischemia-reperfusion injury (IRI), which is triggered by a transient reduction or cessation of blood flow followed by reperfusion, is a significant cause of acute kidney injury (AKI). IRI can lead to acute cell death, tissue injury and even permanent organ dysfunction. In the clinic, IRI contributes to a higher morbidity and mortality and is associated with an unfavorable prognosis in AKI patients. Unfortunately, effective clinical drugs to protect patients against the imminent risk of renal IRI or treat already existing AKI are still lacking. Fibroblast growth factors (FGFs) are important regulators of key biological and pathological processes, such as embryonic development, metabolic homeostasis and tumorigenesis through the regulation of cell differentiation, migration, proliferation and survival. Accumulating evidence suggests that altered expression of endogenous FGFs is associated with IRI and could be instrumental in mediating the repair process. Therefore, FGFs have been proposed as potential biomarkers in the clinic. More importantly, exogenous FGF ligands have been reported to protect against renal IRI and display promising features for therapy. In this review, we summarize the evidence and mechanisms of AKI following IRI with a focus on the therapeutic capacity of several members of the FGF family to treat AKI after IRI.